Modified filter membrane as well as preparation method and application thereof

By constructing an electrostatic selection separation layer on the surface of the filter membrane, the cationically modified guar gum, chitosan quaternary ammonium salt and sodium dodecyl sulfonate are independently loaded, and the resistance of the filter membrane to residual chlorine is solved. The problem of poor degree has achieved a modified filter membrane with good oxidation resistance, extending its service life and reducing its use cost.

CN119186291AActive Publication Date: 2024-12-27NINGBO FOTILE KITCHEN WARE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310758244.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

The existing filter membrane materials have poor tolerance to residual chlorine in tap water, which is easy to oxidize, resulting in shortening of service life. In addition, existing methods may cause bacteria and odor in the membrane module when removing residual chlorine, and increase the use of equipment core replacement. Frequency and cost of use.

Method used

By constructing an electrostatic selection separation layer on the surface of the polyacrylonitrile film, the electrostatic layer of cation modified guar gum and chitosan quaternary ammonium salt and sodium dodecyl sulfonate or sodium dodecylbenzenesulfonate were loaded independently using cationically modified guar gum and chitosan quaternary ammonium salts and electrostatic layer of sodium dodecyl sulfonate or sodium dodecylbenzenesulfonate. , form a modified filter membrane with good oxidation resistance to reduce the impact on residual chlorine.

Benefits of technology

The modified filter membrane maintains good oxidation resistance under high concentration residual chlorine environment, extends service life, and maintains a 98.2% magnesium sulfate removal rate and stable flow rate under 2ppm residual chlorine conditions, reducing the requirements for pretreatment. Improves user experience and economics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004306335350000081
    Figure BDA0004306335350000081
  • Figure BDA0004306335350000091
    Figure BDA0004306335350000091
  • Figure BDA0004306335350000101
    Figure BDA0004306335350000101
Patent Text Reader

Abstract

The invention discloses a modified filter membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, contacting a polyacrylonitrile membrane with carboxyl on the surface with a first solution to obtain a filter membrane I; the solute of the first solution comprises cation modified guar gum and chitosan quaternary ammonium salt; s21, contacting the filter membrane I with a second solution to obtain a filter membrane II; the solute of the second solution comprises sodium dodecyl sulfate and / or sodium dodecyl benzene sulfonate; and S31, carrying out a cross-linking reaction on the filter membrane II and a cross-linking agent to obtain the modified filter membrane. The prepared modified filter membrane has the advantages of being good in oxidation resistance and long in service life, the requirement of a water purification system for pretreatment can be lowered, and the modified filter membrane is economical and convenient to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention specifically relates to a modified filter membrane and a preparation method and application thereof. Background Art

[0002] Residual chlorine in tap water has an antibacterial effect. However, the selective separation layer of the nanofiltration membrane and reverse osmosis membrane materials currently used in the field of water purification is mostly polyamide. This material has poor tolerance to residual chlorine and is easily oxidized by residual chlorine during the purification process, thereby reducing the service life of the membrane.

[0003] In the prior art, in order to prevent the influence of oxidizing substances such as residual chlorine on the filter membrane, an additional activated carbon filter is usually added to the front end of the membrane filter element to remove the residual chlorine, thereby preventing the residual chlorine from affecting the membrane assembly. However, this method removes the residual chlorine before the nanofiltration or reverse osmosis membrane, which may cause bacteria to grow in the water in the membrane assembly, produce disinfection byproducts that are harmful to human health, and even cause the membrane assembly to stink; and this configuration leads to frequent core replacement of water purification equipment, which increases the cost of use and makes the user experience poor. Summary of the invention

[0004] In order to overcome the defects of the prior art that the filter membrane has poor oxidation resistance and is easily oxidized by residual chlorine in tap water, thus reducing its service life, the present invention provides a modified filter membrane and its preparation method and application. The modified filter membrane of the present invention has the advantages of good oxidation resistance and long service life, can reduce the requirements for pretreatment of the water purification system, and is economical and convenient to use.

[0005] The present invention provides a method for preparing a modified filter membrane, which includes the following method 1 or method 2:

[0006] Method 1:

[0007] S1. contacting a polyacrylonitrile membrane having a carboxyl group on its surface with a first solution to obtain a filter membrane Ⅰ; the solute of the first solution comprises a cation-modified guar gum and a chitosan quaternary ammonium salt;

[0008] S21. contacting the filter membrane I with a second solution to obtain a filter membrane II; the solute of the second solution comprises sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate;

[0009] S31. cross-linking the filter membrane II with a cross-linking agent to obtain the modified filter membrane;

[0010] Method 2:

[0011] S1. contacting a polyacrylonitrile membrane having a carboxyl group on its surface with a first solution to obtain a filter membrane Ⅰ; the solute of the first solution comprises a cation-modified guar gum and a chitosan quaternary ammonium salt;

[0012] S22. cross-linking the filter membrane Ⅰ with a cross-linking agent to obtain a filter membrane Ⅰ ';

[0013] S32. Contacting the filter membrane I' with a second solution to obtain the modified filter membrane; the solute of the second solution includes sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate.

[0014] In the present invention, "cationically modified guar gum and chitosan quaternary ammonium salt" and "sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate" are autonomously installed layer by layer on the surface of the polyacrylonitrile membrane through electrostatic action to construct a selective separation layer. The combination of electrostatic force is not easily affected by oxidants such as residual chlorine in water, thereby bringing about a good antioxidant effect.

[0015] In the present invention, the polyacrylonitrile membrane can be purchased from the market or prepared by conventional preparation methods in the art. The preparation method preferably includes the following steps: preparing a membrane from a casting liquid, and then performing a hydrolysis reaction; the casting liquid includes polyacrylonitrile and a solvent.

[0016] The mass fraction of the polyacrylonitrile is preferably 10%-30%, such as 18%; and the solvent is preferably N-methylpyrrolidone.

[0017] Among them, the preparation method of the casting liquid can be to stir polyacrylonitrile under water bath conditions to dissolve it in the solvent, and then degassing it; the polyacrylonitrile is preferably dried first; the temperature of the water bath is preferably 75°C; the time of the water bath is preferably 5-7h; the degassing is preferably carried out at 50°C; the degassing time is preferably 12h.

[0018] The method for preparing the casting liquid into a film can be an immersion precipitation phase inversion method, which can be specifically: subjecting the casting liquid to film scraping, phase inversion and solvent removal in sequence;

[0019] The film scraping process is preferably to adjust the micrometer on the film scraping device to accurately control the distance between the scraper and the glass plate, so that the distance is maintained at 200 μm, and then pour the casting liquid near the scraper, and slide the scraper at a uniform speed to spread the casting liquid on the glass plate.

[0020] The phase inversion process is preferably to immerse the material obtained by scraping the film in a coagulation bath after pre-evaporation, so that the film is peeled off from the glass plate and solidified; the coagulation bath is more preferably water.

[0021] The process of removing the solvent is preferably to soak the cured membrane material in distilled water. The soaking time is more preferably more than 24 hours, and the distilled water is replaced every 12 hours.

[0022] The hydrolysis reaction is preferably carried out by first performing an alkali treatment and then an acid treatment. After the above treatment, the cyano groups on the membrane surface are converted into carboxyl groups, which are negatively charged in water.

[0023] The alkali treatment is preferably carried out in an aqueous solution; the concentration of the alkali in the aqueous solution is more preferably 10%; sodium hydroxide is preferably used for the alkali treatment; the alkali treatment time is preferably 30 minutes; and the alkali treatment temperature is preferably 40° C. After the alkali treatment, the surface color of the membrane is yellow.

[0024] The acid treatment is preferably carried out in an aqueous solution; the concentration of the acid in the aqueous solution is more preferably 0.2 mol / L; hydrochloric acid is preferably used for the acid treatment; the time of the acid treatment is preferably 3 hours; the temperature of the acid treatment is preferably room temperature. After the acid treatment, the surface of the membrane changes from yellow to milky white, and active groups such as carboxyl groups are generated on the surface.

[0025] After the alkali treatment, it is preferred to first wash with distilled water and then perform the acid treatment. The purpose of washing is to remove the alkali remaining on the membrane surface.

[0026] After the acid treatment, it is preferred to use distilled water for washing, and then place the polyacrylonitrile membrane in distilled water for standby use. If it is not used for a long time, potassium bisulfite can be added to the distilled water to prevent bacteria from growing on the membrane surface.

[0027] In the present invention, the cationic modified guar gum (CGG) is a quaternary ammonium salt obtained by modifying the natural polysaccharide guar gum by a conventional method in the art, and its chemical name is guar hydroxypropyltrimethylammonium chloride. The cationic modified guar gum is named Polyquaternium-55 by the US CTFA.

[0028] In the present invention, the chitosan quaternary ammonium salt (HACC) is a chitosan high-grade derivative obtained by modifying the natural polysaccharide chitosan by a conventional method in the art, and its full name is hydroxypropyltrimethylammonium chloride chitosan.

[0029] Chitosan and guar gum are natural polysaccharides with huge production. Quaternary ammonium salts can be obtained by modifying the two natural polysaccharides. CGG, as a natural polyelectrolyte, will ionize chloride ions in water, and its chain is positively charged. HACC is the product of quaternization of free amino groups on sugar residues on the chitosan molecular chain. By quaternizing chitosan, the water solubility of chitosan is improved. The two substances are positively charged in aqueous solution and can bind to the surface of polyacrylonitrile membrane through electrostatic action to construct a separation layer.

[0030] In the present invention, the cross-linking agent can be a conventional substance in the art that can cause CGG and HACC to undergo a cross-linking reaction, preferably glutaraldehyde and / or ethylene glycol. The cross-linking agent can cause a cross-linking reaction between the cationic modified guar gum and the chitosan quaternary ammonium salt.

[0031] In step S1, the concentration of the first solution may be 3%-8%, for example, 5%.

[0032] In step S1, the mass ratio of the cationic modified guar gum to the chitosan quaternary ammonium salt may be (0.5-3):1, preferably (1-2.5):1, such as 0.5:1, 2:1 or 3:1.

[0033] In step S1, the mass ratio of the polyacrylonitrile membrane to the solute of the first solution may be (2-4):1, for example, 3:1.

[0034] In step S1, the contact operation can be to immerse the polyacrylonitrile membrane in the first solution; or, to coat the first solution on the polyacrylonitrile membrane; during the contact process, CGG and HACC are adsorbed to the carboxyl groups on the surface of the polyacrylonitrile membrane through electrostatic action to self-assemble and construct a separation layer structure.

[0035] In step S1, the contact time may be 20-120 min, preferably 30 min-90 min, such as 30 min, 60 min or 90 min.

[0036] In step S1, the temperature of the contacting system may be 20°C-40°C, for example, 25°C.

[0037] In the present invention, the filter membrane I is a filter having positively charged groups introduced on the surface of the polyacrylonitrile.

[0038] In the present invention, the filter membrane I' is a cross-linking reaction between the cationic modified guar gum and chitosan quaternary ammonium salt on the filter membrane I and a cross-linking agent.

[0039] In step S21 or step S32, the concentration of the second solution may be 0.5%-1.5%, for example, 0.5%, 1.0% or 1.5%.

[0040] In step S21 or step S32, the contact operation may be to immerse the filter membrane I or the filter membrane I' in the second solution; or, to coat the second solution on the filter membrane I or the filter membrane I'; during the contact process, "sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate" acts as a negative electrolyte and adsorbs the positively charged groups on the surface of the filter membrane II or the filter membrane I' through electrostatic action to self-assemble and construct a separation layer structure.

[0041] In step S21 or step S32, the contact time may be 20-120 min, preferably 30-90 min, for example 30 min, 60 min or 90 min.

[0042] In step S21 or step S32, the temperature of the contact system may be 20°C-40°C, for example, 25°C.

[0043] In step S21 or step S32, the mass ratio of the polyacrylonitrile membrane to the solute may be (1-3):1, for example, 3:1.

[0044] In the present invention, the filter membrane II is obtained by introducing negatively charged groups on the surface of the filter membrane I.

[0045] In step S31 or step S22, the mass ratio of the cross-linking agent to the polyacrylonitrile membrane may be (0.1-1):100, for example, 0.1:100, 0.8:100, 0.9:100 or 1:100.

[0046] In step S31 or step S22, the cross-linking reaction is preferably carried out in an aqueous solution; in the raw material system of the cross-linking reaction, the concentration of the cross-linking agent is preferably 2%-5%, for example 5%.

[0047] In some specific embodiments, the mass ratio of the cross-linking agent solution to the polyacrylonitrile membrane is 1:10.

[0048] In step S31 or step S22, the cross-linking reaction time may be 20-40 minutes, for example, 30 minutes.

[0049] In step S31 or step S22, the temperature of the cross-linking reaction may be 20°C-40°C, for example 25°C.

[0050] The present invention also provides a modified filter membrane prepared by the above-mentioned preparation method.

[0051] The present invention also provides a modified filter membrane, which comprises a polyacrylonitrile-based membrane and a selective separation layer; the polyacrylonitrile-based membrane and the selective separation layer are combined by electrostatic action; wherein the surface of the polyacrylonitrile-based membrane contains carboxyl groups; the selective separation layer is composed of the "cationically modified guar gum and chitosan quaternary ammonium salt" and the "sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate" combined by electrostatic action.

[0052] The present invention also provides application of the modified filter membrane as mentioned above in the field of water treatment.

[0053] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0054] The reagents and raw materials used in the present invention are commercially available.

[0055] The positive and progressive effects of the present invention are:

[0056] The present invention constructs a selective separation layer on the surface of the polyacrylonitrile membrane by electrostatic layer-by-layer self-assembly, so that the modified filter membrane has good overall antioxidant properties and can withstand the influence of higher concentrations of residual chlorine without losing the calcium and magnesium ion removal effect during use. When the residual chlorine concentration is 2ppm, after passing 8000L of water, it still has a magnesium sulfate removal rate of 98.2% and a flow rate of 1.38L / min, and the magnesium sulfate removal rate is equivalent to the effect when the flow rate and the water flow rate are 0. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 Schematic diagram of the effect test device of the modified filter membrane prepared in Examples 1-13 of the present invention and Comparative Examples 1-3 (1-nitrogen cylinder, 2-buffer tank, 3-nanofiltration cup, 4-magnetic stirrer, 5-liquid inlet, 6-modified filter membrane). DETAILED DESCRIPTION

[0058] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0059] The polyacrylonitrile used in the present invention was purchased from Qilu Chemical Co., Ltd., and its viscosity average molecular weight was 5200;

[0060] The cationic modified guar gum used in the present invention was purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0061] The chitosan quaternary ammonium salt used in the present invention is purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0062] Example 1

[0063] (1) Stir polyacrylonitrile in a water bath at 75°C for 6 hours to dissolve it in N-methylpyrrolidone, and then degasse it at 50°C for 12 hours to obtain a casting solution; then adjust the micrometer on the scraping device to accurately control the distance between the scraper and the glass plate, so that the distance is maintained at 200 μm, then pour the casting solution near the scraper, and slide the scraper at a uniform speed to spread the casting solution on the glass plate, and then immerse it in water after pre-evaporation for 30 seconds to solidify the film and separate it from the glass plate, and wash the solidified film with distilled water , and then soak it in distilled water for at least 24 hours. During the soaking process, the water needs to be changed every 12 hours to completely remove the solvent NMP in the membrane; then the obtained membrane is placed in a 10% sodium hydroxide solution at 40°C for 30 minutes, at which time the color of the PAN surface turns yellow. After multiple washings, it is treated with a 0.2 mol / L hydrochloric acid solution at room temperature for 3 hours to generate active groups such as carboxyl groups on the PAN surface. At this time, the surface color of PAN turns milky white, and then it is washed with distilled water and placed in distilled water for standby use;

[0064] (2) soaking PAN in CGG / HACC solution for a certain period of time to obtain filter membrane I;

[0065] (3) soaking the filter membrane I obtained in step (2) in a sodium dodecyl sulfate solution for a certain period of time to obtain filter membrane II;

[0066] (4) The filter membrane II is subjected to a cross-linking reaction in a glutaraldehyde solution. After a period of time, the unreacted glutaraldehyde is washed away with distilled water to obtain a modified filter membrane.

[0067] The material dosage and process conditions of Examples 1-13 and Comparative Examples 1-3 are shown in Tables 1 and 2, and the unlisted conditions of other Examples and Comparative Examples are the same as those of Example 1.

[0068] Embodiment 14

[0069] (1) Stir polyacrylonitrile in a water bath at 75°C for 6 hours to dissolve it in N-methylpyrrolidone, and then degasse it at 50°C for 12 hours to obtain a casting solution; then adjust the micrometer on the scraping device to accurately control the distance between the scraper and the glass plate, so that the distance is maintained at 200 μm, then pour the casting solution near the scraper, and slide the scraper at a uniform speed to spread the casting solution on the glass plate, and then immerse it in water after pre-evaporation for 30 seconds to solidify the film and separate it from the glass plate, and wash the solidified film with distilled water , and then soak it in distilled water for at least 24 hours. During the soaking process, the water needs to be changed every 12 hours to completely remove the solvent NMP in the membrane; then the obtained membrane is placed in a 10% sodium hydroxide solution at 40°C for 30 minutes, at which time the color of the PAN surface turns yellow. After multiple washings, it is treated with a 0.2 mol / L hydrochloric acid solution at room temperature for 3 hours to generate active groups such as carboxyl groups on the PAN surface. At this time, the surface color of PAN turns milky white, and then it is washed with distilled water and placed in distilled water for standby use;

[0070] (2) soaking PAN in CGG / HACC solution for a certain period of time to obtain filter membrane I;

[0071] (3) cross-linking the filter membrane I in a glutaraldehyde solution, and after a period of time, washing away the unreacted glutaraldehyde with distilled water to obtain the filter membrane I';

[0072] (4) The filter membrane I' obtained in step (3) is immersed in a sodium dodecyl sulfate solution for a certain period of time to obtain a modified filter membrane.

[0073] The specific material dosage and process parameters are shown in Tables 1 and 2.

[0074] Table 1

[0075]

[0076] Table 2

[0077]

[0078] Effect Example

[0079] 1. Magnesium ion removal rate

[0080] A certain area of ​​the modified filter membranes prepared in Examples 1-13 and Comparative Examples 1-3 was fixed in a nanofiltration test device. Figure 1 As shown, a certain concentration of magnesium sulfate solution is prepared and its TDS value is tested (recorded as TDS0). The nanofiltration membrane is compacted with solvent for 45 minutes at room temperature and 0.5MPa (N2), and the TDS of the solution passing through the membrane is tested (recorded as TDS1). Before each test, the solvent flow rate is roughly stable before testing.

[0081] Magnesium ion removal rate = 1-(TDS1 / TDS0)

[0082] 2. Diaphragm flux

[0083] A certain area of ​​the modified filter membranes prepared in Examples 1-13 and Comparative Examples 1-3 was fixed in a nanofiltration test device. Figure 1 As shown, the nanofiltration membrane is compacted with solvent for 45 minutes at room temperature and 0.5MPa (N2), the mass m of water passing through the membrane is tested, and the volume V is calculated. Before each test, the solvent flow is roughly stable before testing. That is, under the condition of a certain pressure, the volume V of the solvent passing through the nanofiltration membrane for a certain time t is tested. The formula for calculating the flux F and permeation flux P of the modified filter membrane is:

[0084]

[0085]

[0086] Where: ΔP is the operating pressure, unit is bar;

[0087] V is the volume of the solvent dripped out during time t, in L;

[0088] A is the effective area of ​​the membrane module, unit: m 2 ;

[0089] t is the sampling time, in h.

[0090] The test results of the above effects are shown in Table 3.

[0091] Table 3

[0092]

[0093]

[0094] It can be seen from the data in Table 3 that the flux of the modified filter membrane prepared by the present invention is 6L / m 2 h, the optimal flux can reach 7.6L / m 2 ·h or more; the removal rate of magnesium sulfate is more than 73%, and more preferably can reach more than 92%.

[0095] Compared with Example 1, the difference between Comparative Examples 1-2 is that only one of CGG and HACC is used in the comparative examples, and the flux of the membrane assembly composed of the modified filter membrane is only 6.6 or 6.8, which is more than 17% lower than that of Example 1, and the removal rate of magnesium sulfate is also more than 15% lower than that of Example 1. It can be seen that CGG must be combined with HACC, combined with the carboxyl group on PAN through electrostatic force, and combined with other features to achieve the good flux and magnesium sulfate removal efficiency of the present invention. This may be because CGG and HACC are cross-linked under the action of the cross-linking agent to form an interpenetrating polymer network structure, and the structure of the membrane is enhanced by mutual entanglement between the polymer networks, so the performance of the membrane is better when the two are used together.

[0096] The difference between Comparative Example 3 and Example 1 is that sodium dodecyl sulfate is replaced by sodium pentadecyl sulfate. Although a flux equivalent to that of the example can be obtained, its removal effect on magnesium sulfate is poor. The measured magnesium sulfate removal rate is only 58%, which is 26% lower than that of Example 1. This may be due to the fact that the molecular chain of sodium pentadecyl sulfate is longer, the proportion of charged functional groups is lower, the electrostatic binding force is insufficient, and it is easy to detach during the use of the membrane.

[0097] Examples 1-9 and Examples 12-13 show the effects of the time for treating PAN membrane with CGG / HACC solution and the time for treating filter membrane I with sodium dodecyl sulfate solution on the effect. It can be seen that the longer the treatment time, the better.

[0098] Compared with Example 1, Examples 10-11 reflect the influence of the mass ratio of CGG and HACC on the effect. When the proportion of CGG increases, the flux of the modified filter membrane and the removal of magnesium sulfate will first increase and then decrease. Therefore, it is necessary to select a suitable ratio to obtain good results. (3) The modified filter membrane prepared in Example 4 was made into a household standard 3013 type membrane assembly, without adding a pre-treatment filter element, and directly passed 2PPM residual chlorine aqueous solution to test its magnesium ion removal rate. The results are shown in Table 4.

[0099] Table 4

[0100] Residual chlorine concentration (ppm) Membrane module flow rate (L / min) Magnesium sulfate removal rate (%) Water flow rate (L) 2 1.42 98.5 0 2 1.40 98.4 2000 2 1.40 98.6 4000 2 1.39 98.4 6000 2 1.38. 98.2 8000

[0101] It can be seen from Table 4 that the membrane assembly can withstand the influence of 2ppm residual chlorine concentration, and the flow rate and sulfate removal rate are not greatly changed after passing 8000L of water. The residual chlorine concentration in tap water is usually 0.2-0.4ppm, which is lower than the test concentration of the present invention. It can be seen that the modified filter membrane of the present invention can have good antioxidant performance when applied to water treatment.

Claims

1. A method for preparing a modified filter membrane, characterized in that: It includes the following method 1 or method 2: Method 1: S1. contacting a polyacrylonitrile membrane having a carboxyl group on its surface with a first solution to obtain a filter membrane Ⅰ; the solute of the first solution comprises a cation-modified guar gum and a chitosan quaternary ammonium salt; S21. contacting the filter membrane I with a second solution to obtain a filter membrane II; The solute of the second solution includes sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate; S31. mixing the filter membrane II with a cross-linking agent to cause a cross-linking reaction to obtain the modified filter membrane; Method 2: S1. contacting a polyacrylonitrile membrane having a carboxyl group on its surface with a first solution to obtain a filter membrane Ⅰ; the solute of the first solution comprises a cation-modified guar gum and a chitosan quaternary ammonium salt; S22. The filter membrane Ⅰ is mixed with a cross-linking agent to undergo a cross-linking reaction to obtain a filter membrane Ⅰ '; S32. contacting the filter membrane Ⅰ' with the second solution to obtain the modified filter membrane; The solute of the second solution includes sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate.

2. The method for preparing the modified filter membrane according to claim 1, characterized in that: In step S1, the concentration of the first solution is 3%-8%, for example 5%; And / or, in step S1, the mass ratio of the cationic modified guar gum to the chitosan quaternary ammonium salt is (0.5-3):1, preferably (1-2.5):1, for example 2:1; And / or, in step S1, the mass ratio of the polyacrylonitrile membrane to the solute of the first solution is (2-4):1, for example, 3:

1.

3. The method for preparing the modified filter membrane according to claim 1, characterized in that: In step S21 or step S32, the concentration of the second solution is 0.5%-1.5%, for example, 0.5%, 1.0% or 1.5%; And / or, in step S21 or step S32, the mass ratio of the polyacrylonitrile membrane to the solute is (1-3):1, for example, 3:1; And / or, in step S31 or step S22, the mass ratio of the cross-linking agent to the polyacrylonitrile membrane is (0.1-1):100, for example, 0.1:100, 0.8:100, 0.9:100 or 1:

100.

4. The method for preparing the modified filter membrane according to claim 1, characterized in that: In step S1, the contact time is 20-120 min, preferably 30 min-90 min, for example 30 min, 60 min or 90 min; And / or, in step S1, the temperature of the contacting system is 20°C-40°C, for example, 25°C; And / or, in step S1, the contacting operation is to immerse the polyacrylonitrile membrane in the first solution; or to coat the first solution on the polyacrylonitrile membrane; And / or, in step S21 or step S32, the contact time is 20-120 min, preferably 30-90 min, for example 30 min, 60 min or 90 min; And / or, in step S21 or step S32, the temperature of the contacting system is 20°C-40°C, for example, 25°C; And / or, in step S21 or step S32, the contacting operation is to immerse the filter membrane I in step S21 or the filter membrane I' in step S32 in the second solution; or, to coat the second solution on the filter membrane I or the filter membrane I'.

5. The method for preparing the modified filter membrane according to claim 1, characterized in that: In step S31 or step S22, the cross-linking reaction is carried out in an aqueous solution; in the raw material system of the cross-linking reaction, the concentration of the cross-linking agent is preferably 2%-5%, for example 5%; And / or, the cross-linking agent is glutaraldehyde and / or ethylene glycol; And / or, in step S31 or step S22, the cross-linking reaction time is 20-40 min, for example, 30 min; And / or, in step S31 or step S22, the temperature of the cross-linking reaction is 20°C-40°C, for example, 25°C.

6. The method for preparing a modified filter membrane according to claim 1, characterized in that: The method for preparing the polyacrylonitrile film containing carboxyl groups on the surface comprises the following steps: preparing a film from a casting liquid, and then performing a hydrolysis reaction; the casting liquid comprises polyacrylonitrile and a solvent; Wherein, the mass fraction of the polyacrylonitrile is preferably 10%-30%, for example 18%; the solvent is preferably N-methylpyrrolidone; The method for preparing the casting solution is preferably to stir polyacrylonitrile in a water bath to dissolve it in a solvent, and then perform a degassing treatment; the polyacrylonitrile is preferably dried first; the temperature of the water bath is preferably 75°C; the time of the water bath is preferably 5-7h; the degassing is preferably performed at 50°C; the degassing time is preferably 12h; Wherein, the method for preparing the casting solution into a film is preferably to subject the casting solution to film scraping, phase conversion and solvent removal in sequence; The hydrolysis reaction is preferably carried out by first performing an alkali treatment and then performing an acid treatment.

7. The method for preparing the modified filter membrane according to claim 6, characterized in that: The film scraping process is to adjust the micrometer on the film scraping device to control the distance between the scraper and the glass plate to be maintained at 200 μm, then pour the casting liquid near the scraper, and slide the scraper at a uniform speed to spread the casting liquid on the glass plate; And / or, the phase inversion process is to pre-evaporate the material obtained by scraping the film and then immerse it in a coagulation bath, so that the film is peeled off from the glass plate and solidified; the coagulation bath is preferably water; And / or, the process of removing the solvent is to soak the cured membrane material in distilled water, the soaking time is preferably more than 24 hours, and the distilled water is replaced every 12 hours; And / or, the alkali treatment is carried out in an aqueous solution; the concentration of the alkali in the aqueous solution is preferably 10%; the alkali treatment is preferably carried out using sodium hydroxide; the alkali treatment time is preferably 30 minutes; the alkali treatment temperature is preferably 40°C; And / or, the acid treatment is carried out in an aqueous solution; the concentration of the acid in the aqueous solution is preferably 0.2 mol / L; the acid treatment is preferably carried out using hydrochloric acid; the time of the acid treatment is preferably 3 hours; the temperature of the acid treatment is preferably 20-40° C., for example 25° C.; and / or, after the alkali treatment, washing with distilled water; And / or, after the acid treatment, washing is performed using distilled water.

8. A modified filter membrane, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 7.

9. A modified filter membrane, characterized in that: The modified filter membrane comprises a polyacrylonitrile membrane and a selective separation layer; the polyacrylonitrile membrane is combined with the selective separation layer through electrostatic action; wherein the surface of the polyacrylonitrile membrane contains carboxyl groups; the selective separation layer is combined with "cationically modified guar gum and chitosan quaternary ammonium salt" and "sodium dodecyl sulfonate and / or sodium dodecylbenzene sulfonate" through electrostatic action.

10. Use of the modified filter membrane according to claim 8 or 9 in the field of water treatment.

Citation Information

Patent Citations

  • Method for raising retention rate and drainability of slurry of tobacco sheet by papermaking process

    CN102767117A

  • Preparation method of quaternary ammonium salt type cationic polymer modified chitosan nanofiltration membrane

    CN103285742A